Bias Sequences and Turn-Taking in the Validation of the Small Group Oral Examination - Dávid, Gergely A. (Working Papers in Language Pedagogy, 2019)
This research originated in an interest in the characteristics of communication in a group oral test. The researcher’s attention was directed towards its turn-taking mechanisms and how communication is shaped in groups of three. The investigation of the test discourse, with reference to insights and predictions from Conversation Analysis, yielded external validity evidence for the conversational nature of the interaction in this test. The findings support the claim that in Phase two of the group oral test the interaction is sufficiently conversational. True to the nature of conversation, each of the recorded exams contained bias sequences, in which interaction involves only two of the speakers from time to time. The findings also suggest a research-based rationale for the number of speakers desirable in a group oral test in that it may be a happy choice to examine students in threes, rather than twos or larger numbers.